Pengaruh Pajak Daerah dan Retribusi Daerah Terhadap Kemandirian Keuangan Daerah - Dimas Ariyo Dewantoro (Journal of Innovation in Management, Accounting and Business, 2022)
The independence of the region in regional autonomy can be seen through the ability of the region's financial resources to be able to develop the region. This study aims to determine the effect of local taxes and regional levies partially and simultaneously on regional financial independence in district/city governments in West Java Province in 2016-2018. In this study, the approach used is a descriptive and verification approach. The type of data used in this study is poll data or panel funds. The study uses secondary data sourced from the Directorate General of Regional Government Fiscal Balance (DJPKPD) through its official website www.djpkpd.go.id. The population taken in this study were all regencies/cities in West Java Province, totaling 27 regencies/cities, consisting of 18 regencies and 9 cities. The results of this study indicate that partially local taxes have a significant positive effect on regional financial independence and regional levies also have a significant positive effect on regional financial independence. However, simultaneously local taxes and regional levies have a significant positive effect on regional financial independence.